A Comparative Case Study on the Challenges Encountered by Philippine Private and Public Educational Institutions with their Existing Management Information System - Zulueta, Ma. Cristina E.; Buno, Rona Mae V.; Cruz, Aaron C. Dela; Sagun, Angelita J.; Buenaventura, Michaela DC San; Talidano, Aileen S.; Cabrera, Wendell C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
For the last two years, all Philippine educational institutions had to adapt flexible learning. All personnel and students underwent orientation and training to their institution’s Management Information System (MIS). These institutions are utilizing either MIS mandated by the Department of Education, subscribed to or created by the institution itself. Challenges and concerns have been noted on the use of these MIS worldwide. Hence, this study elucidated the experiences and challenges of admistrators, faculty and students with their existing MIS among public and private educational institutions in the Philippines. Using a qualitative comparative case study design, the researchers draw the experiences of the participants on their existing MIS. The findings of the study revealed three main themes on the experiences of the participants with their existing MIS: excellent way to systematize and organize, a work in progress and encompassing of all institutional services. On the resolution of concerns and challenges with their MIS, prevailing themes were: having an efficient and expert Information Technology (IT) team, continuous feedback and improvement, and unresolved due to poor internet connectivity. As to how these challenges affected their performance, themes clustered on: improved and more efficient, negatively affected output and efficiency, and unaffected. This study highlighted the importance of proper orientation and training of all personnel and students, for an effective MIS which must be managed by an expert IT team. Despite the challenges encountered, the use of the MIS led to the better performance of the participants’ duties and responsibilities.